Trudna sztuka dorastania a świat bohaterów Aleksandra Kuprina - Bielniak, Nel (Acta Polono-Ruthenica, 2017)
Ambiguous status of adolescents who are no longer children, while not yet adults clearly attracted Aleksandr Kuprin’s attention. In his works we find a large group of teenage girls and boys. There are also both reflections on rapid physical, physiological and psychological changes characteristic of this period as well as their impact on relationships with other people. Apart from that, Kuprin presents nightmares of puberty (fear, rebellion, alienation , loneliness and the desire to be understood at the same time, the need to be part of a group, sacrum of infatuation and profanum of nascent sensuality).